2020
DOI: 10.1002/jcad.12322
|View full text |Cite
|
Sign up to set email alerts
|

Carrying the Burden: Counselors of Color’s Experiences of Microaggressions in Counseling

Abstract: In this secondary analysis using a previous dataset, the authors explored, via a phenomenological research tradition, how 8 counselors of color responded to clients’ microaggressive behaviors. Researchers identified 3 major themes in the data: (a) buffering and bracing for racial microaggressions, (b) experiencing the intrusions of racial microaggressions, and (c) strategizing and responding in session. The authors apply the Multicultural and Social Justice Counseling Competencies (Ratts, Singh, Nassar‐McMilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…As counselors learn more about best practices in terms of both practice and training, they will be able to increase their professional expertise in further developing this action competency. For example, researchers have applied the MSJCC to mental health counselors working with clients in rural communities with high poverty rates (Crumb, Haskins, & Brown, 2019), whereas others have examined the domains and competencies relative to counselors of color and their experiences with microaggressions in the counseling relationship (Branco & Bayne, 2020). Counselor educators have identified pedagogical elements that appear to support the development of these competencies (e.g., Gonzalez‐Voller, Crunk, Barden, Harris, & Belser, 2020; Killian & Floren, 2020), and others have focused on international initiatives and research (Bhat & McMahan, 2016).…”
Section: Implementing the Msjccmentioning
confidence: 99%
“…As counselors learn more about best practices in terms of both practice and training, they will be able to increase their professional expertise in further developing this action competency. For example, researchers have applied the MSJCC to mental health counselors working with clients in rural communities with high poverty rates (Crumb, Haskins, & Brown, 2019), whereas others have examined the domains and competencies relative to counselors of color and their experiences with microaggressions in the counseling relationship (Branco & Bayne, 2020). Counselor educators have identified pedagogical elements that appear to support the development of these competencies (e.g., Gonzalez‐Voller, Crunk, Barden, Harris, & Belser, 2020; Killian & Floren, 2020), and others have focused on international initiatives and research (Bhat & McMahan, 2016).…”
Section: Implementing the Msjccmentioning
confidence: 99%
“…The structure of the day consisted of writing, fellowship, resting, and shared meals. Black male counselor educators are an underrepresented group in counseling education; therefore, a qualitative method was appropriate for this inquiry (Branco & Bayne, 2020;Hays & Singh, 2012). Developed by Moustakas (1990), heuristic inquiry is a form of phenomenology with the assumption of essential processes for investigating the human experience.…”
Section: Methodsmentioning
confidence: 99%
“…Counselors of color bear the unique challenge of navigating issues of race and diversity with White clients (Branco & Bayne, 2020; Spalding et al., 2018), and often experience microaggressions during counseling sessions with White clients (Branco & Bayne, 2020; Haskins et al., 2015). Bayne and Branco (2018) found that counselors of color experienced forms of racial microaggressions when counseling White clients, such as racially charged language, comments or questions about the counselor's appearance or background, shifts in speech such as “my man,” and other more covert responses including limiting disclosures with counselors during sessions.…”
Section: Multicultural Training and Students Of Colormentioning
confidence: 99%